Uncovering the Needs for a Web-based Sign Language Model for Deaf Students with American Sign Language (ASL) - Ufi Ruhama; Yulian, Ryani; Sayidun Nisa Asy-Syifa (Jurnal Pendidikan Indonesia, 2024)
Inclusive education is the right of every individual, including deaf students, to have equal access to English language learning. This research aims to develop a prototype of a web-based sign language learning model, using American Sign Language (WEBSL), for deaf students in learning English. This research uses a Research and Development (R&D) approach with the ADDIE development model. The subject of the study involved 25 deaf students from one of the Special Schools (SLB) in Pontianak City. Data was collected through analysis of the content of English textbooks tailored to deaf students, as well as thematic interviews with experienced teachers, to identify students' learning needs that included inclusivity, accessibility, language clarity, and visual learning preferences. The results of the analysis show the need for an interactive web-based learning model to facilitate deaf students' access to customized English language materials. The prototype developed in this study is designed to suit needs, be interactive, easily accessible, and take into account cultural sensitivities. The conclusion of this study emphasizes the importance of developing adaptive and interactive learning resources, as well as their implications for improving the English skills of deaf students.